Magnitude modelling of HRTF using principal component analysis applied to complex values - Ramos, Oscar Alberto; Tommasini, Fabián Carlos (2021)
Fil: Ramos, Oscar Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro de Investigación y Transferencia en Acústica; Argentina.